Optimisation of Lignin Peroxidase Production Using Locally Isolated Purpureocillium lilacinum Through Factorial Design - S.Y. More; A. M. Datir; Y. R. Baste; G. S. Phad (The Bioscan, 2025)
The lignin peroxidase enzyme is produced by the ligninolytic white rot fungus Purpureocillium lilacinum, which makes it a promising biological treatment tool. Numerous dangerous substances may be broken down by lignin peroxidase. For this technique to be applied effectively, process variables must be optimized to maximize the production of enzymes. An initial screening of medium components was conducted using a Plackett-Burman Design (PBD) with 11 factors. Among these, 8 factors were identified as statistically significant for Lignin Peroxidase production: incubation period, temperature, veratryl alcohol, H2O2, FeSO4, MgSO4, CuSO4, and peptone. The maximum influential factors for production were found to be CuSO4 and temperature. These 8 factors identified by PBD were then selected for further optimization using response surface methodology, specifically the Box-Behnken Design (BBD). The optimized conditions for producing Lignin Peroxidase were: an 11-day incubation period, a temperature of 18°C, 150mM veratryl alcohol, 0.148mM H2O2, 0.1 g/L FeSO4, 0.1 g/L MgSO4, 0.001 g/L CuSO4, and 3.00 g/L peptone. The maximum enzyme activity achieved under these optimized conditions was 115.8. The close agreement between the actual and predicted values of enzyme activity confirms the reliability of the model.